Dermaseptins, Multifunctional Antimicrobial Peptides: A Review of Their Pharmacology, Effectivity, Mechanism of Action, and Possible Future Directions - Bartels, Emiel Jacob Henri; Dekker, Douwe; Amiche, Mohamed (Frontiers in Pharmacology, 2019)
Dermaseptins are a group of α-helical shaped polycationic peptides isolated from the Hylid frogs, with antimicrobial effects against bacteria, parasites, protozoa, viruses in vitro. Besides, anti-tumor effects have been demonstrated. However, few animal experiments and no clinical trials have been conducted thus far. This review summarizes the current knowledge on the pharmacology, ethno pharmacology, effectivity against infectious pathogens and tumors cells and the mechanism of action of the Dermaseptins. Future research should focus on further clarification of the mechanisms of action, the effectivity of Dermaseptins against several cancer cell lines and their applicability in humans.